2022
DOI: 10.1039/d1sc04420f
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of phosphotyrosine-binding oligopeptides with supramolecular target selectivity

Abstract: We demonstrate phage-display screening on self-assembled ligands that enables the identification of oligo-peptides that selectively bind supramolecular targets over their unassembled counterparts. The concept is demonstrated through panning of a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The lead peptide, KVYFSIPWRPM‐NH 2 , was found to bind to the Fmoc‐FYp ligand exclusively in its self‐assembled state with K D =74±3 μM. Circular dichroism, NMR, and molecular dynamics simulations revealed that the peptide interacts through the KVYF terminus and this binding event disrupts the assembled structure [96] …”
Section: Integrated Approaches To Supramolecular Peptide Materials De...mentioning
confidence: 99%
See 1 more Smart Citation
“…The lead peptide, KVYFSIPWRPM‐NH 2 , was found to bind to the Fmoc‐FYp ligand exclusively in its self‐assembled state with K D =74±3 μM. Circular dichroism, NMR, and molecular dynamics simulations revealed that the peptide interacts through the KVYF terminus and this binding event disrupts the assembled structure [96] …”
Section: Integrated Approaches To Supramolecular Peptide Materials De...mentioning
confidence: 99%
“…[28] These FF systems were simulated in 2009 by Marrink et al in the development of the MARTINI forcefield; [21] they found that while they were able to reproduce the degrees of freedom of all-atom forcefields and closely resemble the radial distribution functions, they did not form the expected nanotube morphology. It was subsequently shown that the number of dipeptides simulated (96) would not be sufficient to form a nanotube in this forcefield. Building on this pioneering work, computational studies were developed to explore the sequence space further.…”
Section: Rein V Ulijn Is a Professor Of Nanoscale Systems Chemistry A...mentioning
confidence: 99%
“…This methodology included the peptide phage‐display screening on self‐assembled tyrosine‐phosphate ligands. The resultant oligopeptides identified showed selective binding to supramolecular targets over their unassembled counterpart [39d] . Moreover, the lead 12‐mer peptide KVYSIPWRVPM‐NH 2 with the best binding performance containing aromatic, charged, proline, exhibited the ability to hydrolyze p ‐nitrophenol phosphate substrate with a modest k cat of 10 −5 s −1 .…”
Section: Engineering and Discovery Of Sequence‐encoding Catalytic Fun...mentioning
confidence: 99%
“…Subtle changes in the reactional microenvironment can lead to conformational destabilization, further influencing catalysis. Figure 4 shows examples of the influence of pH in polyproline‐β‐turn‐α‐helix motif [28] (Figure 4A) or of peptide concentration in β‐hairpin like‐structures (Figures 4D & 4E) [39d] . The constrained polyproline‐β‐turn‐α‐helix motif allows the formation of an active site pockets with the correct positioning of catalytic residues and other residues relevant for binding, in a pH‐dependent manner In Figure 4A.…”
Section: Engineering and Discovery Of Sequence‐encoding Catalytic Fun...mentioning
confidence: 99%
“…In recent years, low molecular weight gelators have been increasingly researched due to their interesting properties like self-association in a medium to form an inter-linked network structure for various applications. [1][2][3][4][5][6][7] These gelators can be assembled using various non-covalent interactions including hydrogen bonding, p-p stacking, van der Waals and other interactions to form gels under suitable conditions. 8 The micro-and nano-network structure of hydrogels leads to a highly porous structure, so they can easily entrap numerous water molecules in the gel cavities.…”
Section: Introductionmentioning
confidence: 99%